Perkembangan aplikasi spreadsheet dan pengaruhnya terhadap inovasi pembelajaran berbasis teknologi di dunia pendidikan - Ihsan, Luthfi Nur; Melati, Puput; Jumatiah, Siti (Universitas Madako Tolitoli, 2025)
This article discusses the evolution of spreadsheet applications over time and their relevance to digital transformation in education. Initially used only for basic numerical calculations, spreadsheets have evolved into multifunctional tools that support data analysis, learning evaluation, educational administration management, and technology-based collaborative activities. Applications such as Microsoft Excel and Google Sheets are not only tools for data processing but also play a crucial role in improving the digital competence of teachers and students. Through cloud-based features and real-time collaboration, modern spreadsheets can accelerate the process of inputting grades, developing curricula, analysing learning outcomes, and making data-driven decisions in educational institutions. This study uses a library research approach to analyse the transformation of spreadsheet technology and its impact on the effectiveness of educational management. The results show that the development of spreadsheet applications has made a significant contribution to creating a more efficient, adaptive education system, and one that is oriented towards mastering 21st-century digital literacy.